The Quality Service of JKN Patient Assessed From Tangible Dimension At Rumah Sakit Islam Gigi dan Mulut (RSIGM) Sultan Agung Semarang - Niam, Moh Husnun; Veriyanti, Naila Abhista; Sugiarto, Febia Astiawati (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
The quality of service at the hospital must be optimal so that patient satisfaction is met. One application of service quality, namely the tangible dimension, is still not implemented well and does not have a significant influence on patient satisfaction. This research aims to determine the influence and assessment of the application of tangible dimension elements on patient satisfaction at RSIGM Sultan Agung Semarang. This research method uses analytical observational research (cross sectional) with an accidental sampling technique of 97 respondents. The research instrument used a questionnaire consisting of 15 tangible dimension question items and 5 patient satisfaction question items. Then a reliability validity test, normality test and non-parametric test, namely the Spearman correlation test, were carried out. The research results showed that there was a significant influence of the tangible dimension on patient satisfaction (p=0.000). The implementation of the tangible dimension is good with 54.9% answers being very satisfied and the level of patient satisfaction at RSIGM Sultan Agung Semarang is good with 59.4% answers being very satisfied. The conclusion obtained from this research is that there is an influence between the tangible dimension and the level of patient satisfaction, where the better the implementation of the elements of the tangible dimension, the better the level of patient satisfaction.